PENGARUH FASILITAS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Kelkusa, Alfian; Nurlaela, Nurlaela; Hariyati, Ismi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2025)
This research was conducted to examine the influence of work facilities and work discipline on the performance of Public Health Center employees. This type of research is quantitative with descriptive and verification types. The sample used was a saturated sample of 65 employees. The data used are primary and secondary. Data collection was carried out by observation, interviews and questionnaires. Research data analysis used multiple linear tests and hypothesis testing using the SPSS version 26 application. The research results showed that there was a partial influence on work facilities and work discipline on employee performance. Based on a simultaneous test, work facilities and work discipline influence the performance of employees at the Wosi Health Center, Manokwari district